Synthesis of a Near‐Infrared Fluorescence Turn‐On Probe Based on Dicyanoisophorone for HS−‐Detection in Cancer Cells and Zebrafish in Pure Water Media. Issue 17 (3rd May 2022) - Huang, Xuelong; Lan, Ning; Jiang, Fan; He, Haifeng; Zhong, Jiang
Abstract: It is still a huge challenge to develop novel near‐infrared (NIR) probes with high selectivity and sensitivity for the detection of HS − anions in pure water medium. Herein, a novel dicyanoisophorone‐based NIR fluorescent turn‐on probe for HS − anions is reported. This probe displays a highly selective and sensitive (detection limit: 1.35 μM) with emission wavelength at 675 nm in pure water by using a schiff base group as a selective reaction site for HS − . Moreover, probe DCI‐SB can be used for tracking HS − anions in HeLa cells and zebrafish, indicating that it can be potentially applied for HS − anions sensing in biology fields. Abstract : Insert text for Table of Contents here.A novel dicyanoisophorone‐based near‐infrared fluorescent turn‐on probe DCI‐SB for HS − anions is reported. This probe displays a highly selective and sensitive (detection limit: 1.35 μM) with emission wavelength at 675 nm in pure water by using a schiff base group as a selective reaction site for HS − . Moreover, probe DCI‐SB can be used for tracking HS − anions in HeLa cells and zebrafish, indicating that it can be potentially applied for HS − anions sensing in biology fields.